Effect of owners education and vets communication on therapeutic adherence in pet practice - Dinis, Jorge; Baptista, Catarina Jota; Martins, Ângela; Coelho, Ana Cláudia; Oliveira, Paula A. (Revista de Ciências Agroveterinárias, 2025)
The success of disease treatment in veterinary medicine depends on a correct diagnosis, the choice of an appropriate therapy, and the ability of the animal’s owner to administer the medication correctly. This study aims to identify and understand the factors that interfere with therapeutic adherence (TA), namely the level of education of owners and the influence of veterinary communication, based on questionnaires conducted in a small animal University Hospital in Vila Real, Portugal. “Oversight” was identified by 25% of respondents as the reason for not administering medication properly to their pets. However, when we correlated these answers with owners’ characterization, we found that households made up of more than one person were less likely to forget their treatment regimen (p=0.04). Owners with higher education levels and a more transparent relationship with their veterinarians are more likely to deliver superior health care to their pets. This study suggests that veterinarians should consider these aspects when communicating with the owners to promote a better outcome for their clinical cases. The owners’ perspective regarding veterinarian instructions therapy is crucial to design strategies and to improve TA in the long term.